Sex difference and Allee effects shape the dynamics of sex‐structured invasions. (3rd April 2017) - Shaw, Allison K.; Kokko, Hanna; Neubert, Michael G.
Summary: The rate at which a population grows and spreads can depend on individual behaviour and interactions with others. In many species with two sexes, males and females differ in key life‐history traits (e.g. growth, survival and dispersal), which can scale up to affect population rates of growth and spread. In sexually reproducing species, the mechanics of locating mates and reproducing successfully introduce further complications for predicting the invasion speed (spread rate), as both can change nonlinearly with density. Most models of population spread are based on one sex, or include limited aspects of sex differences. Here we ask whether and how the dynamics of finding mates interact with sex‐specific life‐history traits to influence the rate of population spread. We present a hybrid approach for modelling invasions of populations with two sexes that links individual‐level mating behaviour (in an individual‐based model) to population‐level dynamics (in an integrodifference equation model). We find that limiting the amount of time during which individuals can search for mates causes a demographic Allee effect which can slow, delay, or even prevent an invasion. Furthermore, any sex‐based asymmetries in life history or behaviour (skewed sex ratio, sex‐biased dispersal, and sex‐specific mating behaviours) amplify these effects. In contrast, allowing individuals to mate more than once ameliorates these effects, enabling polygynandrous populations to invade under conditions where monogamously mating populations would fail to establish. We show that details of individuals' mating behaviour can impact the rate of population spread. Based on our results, we propose a stricter definition of a mate‐finding Allee effect, which is not met by the commonly used minimum mating function. Our modelling approach, which links individual‐ and population‐level dynamics in a single model, may be useful for exploring other aspects of individual behaviour that are thought to impact the rate of population spread. Abstract : The authors develop a novel modelling approach that links individual‐level mating behaviour dynamics to population level growth and spread. Although mating dynamics (e.g. mate‐finding Allee effects) are expected to have a strong impact on the establishment and spread of invasive species, few modelling approaches explicitly account for these dynamics.